Plant growth and survival of five introduced and two native/naturalized perennial grass genotypes exposed to two defoliation managements in arid Argentina - Torres, Yanina Alejandra (2013)
The field performance of the native Pappophorum vaginatum, the naturalized Eragrostis curvula and various cultivars of the introduced Achnatherum hymenoides and Leymus cinereus was evaluated as potential forage resources in rangelands of arid Argentina during the warm seasons of 2007/2008 and 2008/2009. Plants of these grass species, obtained from seeds, were transplanted to the field in 2006, when they were 1 year old. During the study years, there were two defoliation managements: plants of all study genotypes either remained undefoliated (controls) or were defoliated twice a year during spring at 5 cm stubble height. Despite tiller number being lower (P < 0·05) on defoliated than on undefoliated plants, and total leaf length per unit basal area being similar (P > 0·05) between defoliation managements by mid-spring, there were no differences (P > 0·05) in dry weight production between defoliated and undefoliated plants in all genotypes at the end of the second growing season. Plants of one or more of the introduced genotypes showed a similar (P > 0·05) or greater (P < 0·05), but not lower, tiller number per plant and per square centimetre, daughter tiller production, total leaf length and dry weight production per unit basal area than the native species at the end of the first and/or second growing seasons. These morphological variables were similar (P > 0·05) or greater (P < 0·05) in the native than in the naturalized genotype. Plant survival, however, was lower (P < 0·05, overall mean = 20%) in the introduced than in the native (>70%) or naturalized (>39%) genotypes at the end of the first or second growing seasons.